So far, so close? Citizens' perception of the presence of international institutions in Brussels - François Foret (Brussels Studies, 2022)
Citizens' perception of the presence of international institutions in Brussels remains understudied. Our study contributes to filling this gap through a survey conducted with a representative sample of Brussels residents in September 2021. The objective is to analyse the representations and practices of the local population with respect to international institutions. Our data show that there is a positive assessment of their contributions to the economy, employment, public goods, identity and culture. These benefits are nevertheless accompanied by perceived disadvantages as regards terrorist risks, integration of immigration deemed excessive and alienation in terms of identity. In conclusion, the world of international institutions seems to coexist and interact with that of ordinary Brussels residents in a relationship of acceptance marked by distance and indifference.